In search of key success factors for E-Learning in Malaysia - Aliah Hanim M. Salleh; Sallehuddin Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2003)
With emerging technologies such as the Internet and e-commerce, a rapidly changing market, chronic shortages of knowledge-workers and more demanding customers, the growing importance of e-learning makes it vital for program managers to know the ingredients of a successful e-learning program. The e-learning industry and hence, the literature on this subject are very much in the embryonic stage in Malaysia. This paper first draws insights from a macro-industry study involving expert interviews with /3 pioneers in the Malaysian e-learning industry. Three performance dimensions describing success at the institutional level that emerged were: managerial imperatives, operational excellence and market responsiveness. Then, it incorporates the findings of another study which took this analysis to the program level. The latter study interviewed another set of five experts at program development and management in e-learning. This was further examined by conducting a focus group discussion with a panel of eight lecturers from a leading e-learning university. Six dimensions of success attributes at the program level were found. These are namely, e-supportive committed management, e-reliable efficient system, e-quality learning content, e-knowledgeable instructors, e-independent resourceful learners and e- supporting external factors.